The Relationship between Lifestyle and Ureum Creatinine Levels in Chronic Kidney Disease (CKD) Patients at Kudungga Hospital, East Kutai - Agustina Banne; DP. Era; Frana Andrianur (Formosa Journal of Science and Technology, 2023)
The aim of this study was to determine the relationship between lifestyle and urea creatinine levels in chronic kidney disease (CKD) patients at Kudungga Regional Hospital, East Kutai. The design of this research was cross sectional with a retrospective approach. The population is 43 patients with chronic kidney failure at Kudungga Regional Hospital from January to March 2023. The sampling technique used total sampling, so the sample totaled 43 patients. Data analysis used the independent sample t test. The characteristics of the respondents were mostly aged between 46-55 years (27.9%), female gender (55.8%), completed high school education (37.2%) and occupation as a housewife (51.2%). The lifestyle of chronic kidney disease patients is unhealthy (58.1%), abnormal urea levels (74.4%) and abnormal creatinine levels (74.4%). There is a relationship between lifestyle and urea levels (p value 0.000) and there is a relationship between lifestyle and creatinine levels (p value 0.002).